Nursing Knowledge Level Regarding Proper Assessment and Methods of Wound Care: Literature Review - Ermalynda Sukmawati; Abigael Grace Prasetiani; Steven Aldo Marcello; Agustina Chriswinda Bura Mare (Adi Husada Nursing Journal, 2026)
The increasing prevalence of chronic wounds, particularly among older adults with diabetes mellitus, requires nurses to possess adequate knowledge and skills in wound assessment and evidence-based wound care to promote healing and prevent complications. This literature review aimed to examine nurses' level of knowledge regarding wound assessment and appropriate wound care methods. A literature review was conducted using secondary data from relevant national and international published articles on nurses' knowledge of wound assessment and management. The reviewed studies consistently demonstrated that nurses with higher levels of knowledge perform more accurate wound assessments and apply appropriate wound care practices, resulting in improved healing outcomes and reduced risk of complications. Conversely, inadequate knowledge may contribute to delayed healing, infection, and poor wound management. Nurses' knowledge is a key factor in effective wound assessment and management. Continuous education and training are essential to enhance nurses' competencies, improve the quality of wound care, accelerate healing, and minimize wound-related complications, particularly in older adults with chronic wounds.